Rethinking Universal Accessibility: a broader approach considering the digital gap - Julio Abascal; Simon D.J. Barbosa; C.A. Nicolle; Panayiotis Zaphiris (2015)
The Universal Accessibility concept is usually formulated in terms that ignore the socio-economic and socio-political context. Therefore it has impact only on a small fraction of the global population of people with disabilities. This issue raises the need for a comprehensive approach that takes into account issues related to literacy, availability of technology, digital literacy, the use of minority languages, etc.